The Influence of Secondhand Clothing Product Quality on Purchase Decisions Among Consumers (A Study on Economics Education Students) - Ode, Fifin; Louhenapessy, William George; Sinay, Francisca Riconita (JENDELA PENGETAHUAN, 2022)
The purpose of this study is to determine the quality of the product to significantly affect the purchase decision on used clothing. The type of research used is quantitative research associative approach. The population in this study is Economic Education Students class of 2019-2022. The sampling technique in this study uses purposive sampling, namely determining samples based on predetermined criteria, namely consumers who often shop for used clothes. The data analysis techniques used in this study are, validity test, reliability test, simple regression analysis test and partial test (t test). Based on the results obtained in this study, product quality has a positive and significant effect on purchasing decisions. Product quality had a 56.0% effect on purchasing decisions while the remaining 44.0% was influenced by other variables not examined in this study.